1993
DOI: 10.1007/bf03160859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depth of flooding on summer water budgets for small diked marshes

Abstract: Water budgets for 10 small diked marshes in Manitoba, Canada were constructed for each of the 6 ice-free months for 5 years. Water levels in the marshes were maintained at 3 levels by pumping: 4 marshes at the average level of the surrounding marsh, 3 at +30 cm, and 3 at +60 cm. Water levels were assigned so that surface water-ground water relationships were replicated. At normal levels, precipitation and evapotranspiration (ET) were the major input and output of water, respectively. Local ground water-surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Simulations illustrated the sensitivity of the model to small changes in growing season evapotranspiration and subsurface flow. Sensitivity of wetland hydrology and vegetation dynamics to growing season evapotranspiration is consistent with hydrologic studies of prairie wetlands (Kadlec 1993). Evapotranspiration is the major water loss in semipermanent prairie wetlands (Shjeflo 1968;Woo and Rowsell 1993) and is expected to change with a changing climate Rosenberg et al 1989;McKenney and Rosenberg 1993).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Simulations illustrated the sensitivity of the model to small changes in growing season evapotranspiration and subsurface flow. Sensitivity of wetland hydrology and vegetation dynamics to growing season evapotranspiration is consistent with hydrologic studies of prairie wetlands (Kadlec 1993). Evapotranspiration is the major water loss in semipermanent prairie wetlands (Shjeflo 1968;Woo and Rowsell 1993) and is expected to change with a changing climate Rosenberg et al 1989;McKenney and Rosenberg 1993).…”
Section: Discussionsupporting
confidence: 77%
“…Evapotranspiration is the major water loss in semipermanent prairie wetlands (Shjeflo 1968;Woo and Rowsell 1993) and is expected to change with a changing climate Rosenberg et al 1989;McKenney and Rosenberg 1993). Seepage inflow and outflow, in contrast, vary considerably among prairie wetlands, but even small daily fluxes can be a significant portion of a wetland water budget over an entire season (Shjeflo 1968;Kadlec 1993;Woo and Rowsell 1993). Calibration of subsurface inputs and evapotranspiration was possible in this study because oflong-term water level data for wetland Pl, and results illustrate the value of such data for developing realistic models.…”
Section: Discussionmentioning
confidence: 99%
“…He argues that actual wetland ET compared to large bodies of open water (ET/Eo ratio) rarely exceeds one and that recent experimental evidence presented within a theoretical context indicates open water evaporates more water than vegetated lakes. Kadlec (1993) also reported that for 10 small diked marshes in Canada, dense emergents reduced total water loss. The data in our study indicates that for summer months, the marsh loses more water through ET than open water and has low ET in January and February when the vegetation is dormant and the resultant litter reduces evaporation by controlling the rate at which water vapor escapes from the water surface.…”
Section: Evapotranspirationmentioning
confidence: 89%
“…However, when carrying out studies on the agriculturally used, drained, and irrigated lowlands with relatively high intra-annual groundwater amplitudes, this element must be included in the water balance investigations. Likewise, storage is often considered a particularly important component of the water balance in connection with the renaturation of existing wetlands or the creation of constructed wetlands (Kadlec, 1993;Spieksma et al, 1996;.…”
Section: Introductionmentioning
confidence: 99%